Calcineurin knockout mice show a selective loss of small spines. (3rd April 2018) - Okazaki, Hitoshi; Hayashi-Takagi, Akiko; Nagaoka, Akira; Negishi, Makiko; Ucar, Hasan; Yagishita, Sho; Ishii, Kazuhiko; Toyoizumi, Taro; Fox, Kevin; Kasai, Haruo
Highlights: Knockout of calcineurin reduced small spines in the prefrontal and visual cortices. The reduction was moderate, possibly due to the presence of intrinsic spine dynamics. Calcineurin knockouts and patients with schizophrenia have similar spine phenotypes. Abstract: Calcineurin is required for long-term depression and activity-dependent spine shrinkage, and calcineurin mutations have been identified in patients with schizophrenia. Moreover, mice with conditional knockout of calcineurin B (CNB-KO) exhibit behavioral abnormalities suggestive of schizophrenia. Changes in the dendritic spines of these mice, however, have not been investigated. We therefore examined the dendritic spines of CNB-KO mice, and observed a significant reduction in small spines and an increase in large spines in the prefrontal and visual cortices. The effect of CNB-KO on the spine sizes was relatively moderate, possibly due to the presence of spontaneous fluctuations (dynamics) in the dendritic spines themselves. Thus, CNB-KO mice showed a spine phenotype similar to those recently reported in patients with schizophrenia.